Influence of hydrological regime on plants of English oak Quercus robur L. under conditions of Volga-Akhtuba floodplain - Anna A. Bakaneva (RUDN Journal of Agronomy and Animal Industries)
Different methods of planting English oak (Quercus robur L.) acorns, one-year-old seedlings and two-year-old saplings on experimental plots of Volga-Akhtuba floodplain in the Astrakhan region, Chernoyarsk district, village of Solenoye Zaymishche were studied. The following variants of hydrological conditions long-duration flooding, short-duration flooding, non-flooding were studied. Forests of the Astrakhan region are experiencing enormous natural and anthropogenic loads, which leads to the degradation of forest phytocenosis. Therefore, such studies are relevant for this region. The purpose of the research was to study the methods of planting English oak (Qurcus rbur) with various planting materials, including acorns, one-year-old seedlings and two-year-old saplings in the floodplain conditions of the Volga River in the village of Solenoye Zaymishche. The data obtained were processed by the method of variance analysis of B.A. Dospekhov (2014) using the Microsoft Excel program. According to the results of the three-year study (20212023), thehighest survival (56 %) was noted under conditions of Volga-Akhtuba floodplain on long-duration flooding site with two-year-old saplings, which exceeded the other variants by 45 times.